Penanganan Kanker Kolorektal Di Rumah Sakit Kanker âDharmaisâ Jakart - PASARIBU, ADIL S (Indonesian Journal of Cancer, 2010)
https://www.scribd.com/doc/43612723/Penanganan-Kanker-Kolorektal-Di-Rumah-Sakit-Kanker-Dharmais-Jakart